A Retrospective Case Series of Anaesthetic Management of Children with Temporomandibular Joint Ankylosis from a Tertiary Level Referral Paediatric Hospital - Ganigara, Anuradha; Ravishankar, Chandrakala Kunigal; Ashwathanarayanashett, Bhavana Dalasanura; Mariam, Mahdiyyah; Vakoda, Chandrika Yabagodu Rama (Journal of Anaesthesia and Pain, 2024)
Background: Children with temporomandibular joint ankylosis (TMJA) are associated with a difficult airway and require special anesthesia management. No clear guidelines have been issued for managing difficult airways in children, especially for TMJA.  Therefore, the aim of this retrospective case study was to understand the difficulties in airway access faced in children with TMJA and to describe the various techniques for successful airway management.Case: We conducted a retrospective review from 2017 to 2022 of 14 children aged 2-14 years who presented for surgical correction of unilateral or bilateral TMJ ankylosis (TMJA) at a pediatric tertiary referral center.  The maximal interincisor distance (MID) and Colorado pediatric airway score (COPUR) were used to plan airway management in these children. Unilateral TMJA was seen in 11 children; the remaining 3 had bilateral TMJA with MID < 1 cm. Flexible fiberoptic intubation was used as an aid to facilitate intubation in a total of five children with MID ≤ 1 cm. Video laryngoscopy and direct laryngoscopy were suitable for visualizing the glottic opening in the remaining children with a midline deviation (MID) greater than 1 cm. Conclusion: Flexible fiberoptic intubation is beneficial for airway management in children with bilateral and/or unilateral TMJA and MID ≤ 1 cm. Children with lesser degrees of mouth opening restriction were successfully managed with video laryngoscopy and direct laryngoscopy for airway control. This preliminary report provides vital information about the decision-making and referral process for children with TMJA, taking into consideration the varying infrastructural resources available in low- and middle-income settings.